Penentuan Parameter Pemotongan Optimal Proses Milling Terhadap Kekasaran Permukaan Baja SKD11 Dengan Metode Taguchi - Muhammad Sobron Yamin Lubis; Steven D; Alfred Briantio; Rosehan Rosehan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
In the milling process, good surface roughness conditions are indicated by low surface roughness values. Surface roughness is formed by the friction of the cutting tools on the surface of the workpiece. Increasing the use of cutting parameters will invariably increase the applied frictional force and faster scratching; however, if there are three cutting parameters used, such as cutting speed, infeed speed, and depth of cut, it is difficult to determine which parameter contributes to the resulting value. Good surface roughness. So based on this, to find out the optimal cutting parameters, this research was carried out. The study was carried out using a milling machine. In the SKD11 Steel material milling process, the surface roughness value of the workpiece is an indicator in determining a good surface condition. SKD11 steel material has a hardness value of 16-20 HRC and is a type of tool steel commonly used as cutting tools, Deep Drawing molds, Drawing Cones, and Compression Molding Dies. By varying the cutting parameters, the workpiece is formed using a milling machine. The cut workpiece is then measured for surface roughness using a surface test tool. Furthermore, to analyze the optimal cutting parameter values for minimal surface roughness, the Taguchi method is used. The results showed that the optimal surface roughness value was obtained from a combination of cutting parameters with a spindle speed of 1800 r/min, a feed rate of 256 mm/min, and a depth of cut of 0.25 mm.